HUBUNGAN MODAL SOSIAL DAN KESEJAHTERAAN EKONOMI MASYARAKAT DESA WISATA PONGGOK, KABUPATEN KLATEN - Deca Melani Kristiar Putri; AR Rohman Taufiq Hidayat; Gunawan Prayitno (Pangripta Sembada : Jurnal Perencanaan Pembangunan, 2026)
Developing tourism villages is a strategy promoted to accelerate the achievement of SDG Goal 1 (No Poverty). However, empirical evidence across various contexts indicates that tourism village development does not always result in the equitable distribution of economic benefits among local communities. A similar phenomenon is observed in Ponggok Village; while it has achieved economic success through tourism, it currently faces challenges such as declining visitor numbers, issues regarding return on investment and profit-sharing systems, and disparities in economic access among residents. These conditions are thought to stem from differences in trust, norms, and social networks among villagers, making social capital a crucial factor in bridging the gap toward equitable, tourism-based economic prosperity. Therefore, this study aims to examine the relationship between these three dimensions of social capital and the economic well-being of the Ponggok Village community. A quantitative approach was employed, utilizing descriptive statistics, a composite index, Chi-Square tests for supplementary analysis, and Spearman correlation tests for the primary analysis. The results indicate that social capital falls into the "good" category (index: 72.33), while economic well-being falls into the "very good" category (index: 83.65). Overall, social capital shows a strong, significant positive relationship with economic well-being (ρ = 0.516; p < 0.001). At the dimensional level, social networks exhibited the strongest relationship (ρ = 0.529), followed by trust (ρ = 0.487) and norms (ρ = 0.409). These findings demonstrate that enhancing economic well-being in tourism villages depends not only on developing the tourism sector itself but also on strengthening social ties that can more inclusively expand community access to information, participation, and economic opportunities.